Contested Urban Futures: Spatial Politics and Urban Redevelopment in Jakarta, 2012-2022 - Tomy Wijaya; Syafruddin Yusuf (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the political dynamics and contentious aspects of urban redevelopment in Jakarta from 2012 to 2022. The research aims to analyze the production, negotiation, and contestation of the city's spatial future by various actors, including the state, capital, and citizens, through regulatory planning, extensive infrastructure initiatives, and quotidian resistance practices. This study employs historical methods and urban historical analysis, utilizing primary sources including provincial spatial planning documents (RTRW, RPJMD), gubernatorial regulations, media archives, and court rulings concerning eviction disputes. Source criticism and interpretation were utilized to elucidate the interaction of modernization narratives, capital accumulation strategies, and community rights. The findings indicate that Jakarta's urban transformation has been propelled by a confluence of top-down governmental policies and the real estate shift facilitating capital accumulation via Transit-Oriented Development projects, reclamation, and mega-infrastructure, alongside grassroots citizen resistance manifested through litigation, advocacy, and the co-production of alternative spaces. These processes generate a spatial arrangement marked by modernization and exacerbating socio-spatial inequality. The study concludes that Jakarta exemplifies contested urbanism, wherein the city functions not merely as a neutral vessel for development but as a political arena influenced by continuous conflicts, negotiations, and compromises. This research enhances global urban studies by providing a nuanced comprehension of spatial politics in the Global South and emphasizing the necessity for inclusive, participatory planning to guarantee that future urban transformations reconcile economic growth with social justice.